(untitled) (Research, Society and Development, 2021)
Objectives: Propose the nursing process to patients infected with COVID-19 based on evidences available about the clinical features of the disease. Methodology: Scoping review performed in april 2020 on electronic databases. Were included original studies conducted with patients infected with the disease, published in portuguese, english and spanish. The studies were selected according with the reccomendation of Preferred Reporting Items for Systematic Reviews and MetaAnalyses. The sample was composed with 17 publications. Results: The detected clinical features allowed the elaboration of nursing diagnostics, results and interventions with focus on the domaines: body temperature, infection, oxigenation/respiration, cardiovascular and gastrointestinal function. Conclusion: The systems of classification NANDA International, Classifications of Nursing Outcomes and Classifications of Nursing Interventions allowed to elaborate diagnostics directed to the evaluation of progression of signs and symptoms and the interventions had as target the combat to the causes of the problems and the monitoring of the clinical conditions of the infected.